A global scoping review of the circumstances of care seeking for abortion later in pregnancy. - Laura E Jacobson; Blair G Darney; Heidi Bart Johnston; Bela Ganatra (PLOS Global Public Health)
Understanding the circumstances of abortions later in pregnancy provides insight about the barriers and delays to timely care. Limited synthesized information is available on these circumstances, especially from low and middle incomes countries. Reviewing what is reported in the literature about the circumstances of abortion later in pregnancy and the methodological approaches used to study this is needed to reveal evidence gaps. The purpose of this study is to describe what is documented and methodological approaches used in existing literature on the circumstances and characteristics associated with seeking care for abortion later in pregnancy reported in population and facility-based studies. We conducted a scoping review of peer-reviewed research in OVID/PubMed, Embase, Scopus, SocIndex, and LILACs from 2007-2024 that described the circumstance, sociodemographic characteristics, population- or facility-based proportion of abortion later in pregnancy (≥12 weeks of gestation or "second trimester") reported in the literature. We screened 2598 records by title and/or abstract and 668 of those by full text. We included 78 studies that described the circumstances around seeking care for abortion later in pregnancy from qualitative data (12 studies); included information on associated characteristics from quantitative data (15 studies); reported a population- (17 studies) or facility-based (45 studies) proportion of abortion later in pregnancy. Prominent themes included health system challenges, late pregnancy recognition, financial challenges, and delayed decision making. Low economic status and adolescence were commonly associated characteristics. Population and facility-based studies lacked standardization when reporting durations of gestation. Facility studies reported a wide variety of populations and number of facilities. Circumstances surrounding abortions later in pregnancy include health system challenges, late pregnancy recognition, financial issues, and delayed decision-making, which intersect to compound and extend delays. More research guided by clear methods and standard definitions when reporting on population and facility-based proportions of abortions later in pregnancy is needed to reveal evidence gaps and better inform policies and programs.